Handbook of research on determining the reliability of online assessment and distance learning - Moura, Ana S.; Reis, Pedro; Cordeiro, M. Natália D. S. (IGI Global, Publisher of Timely Knowledge, 2021)
"This is a collection of pioneering investigations on the methods and applications of digital technologies in the realm of education. It provides a clear and extensive analysis of issues regarding online learning while also offering frameworks to solve these addressed problems" - Provided by publisher.
Keywords: Web-based instruction / Evaluation; Distance education / Evaluation; Educational tests and measurements / Evaluation